NON-FORMAL AND INFORMAL PRESCHOOL EDUCATION: NATURE, TYPES, AND FUNCTIONS - CHYKUROVA, Olha; CHAIKA, Volodymyr; PYSARCHYK, Oksana (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2023)
Abstract. Modern realities impose new demands on preschool education, where, in addition to formal education, informal and non-formal education play an increasingly significant role. These two types of education enrich the knowledge, skills, and abilities of children, contributing to their comprehensive development. The article defines the essence and specificity of informal and non-formal preschool education, distinguishing them from formal education. It explores the impact of informal and non-formal education on the formation of the personality of preschool children, emphasizing their vital role in complementing and expanding the possibilities of formal education. It is established that informal and non-formal education foster the development of cognitive, emotional-volitional, and personal spheres of the child, shaping their creative abilities, independence, initiative, responsibility, and creativity. The main focus is on the importance of informal and non-formal education through the lens of the concept of lifelong learning and educational continuity. It is investigated that informal and non-formal education for preschool children is education obtained outside the formal education system, i.e., kindergarten. It may be associated with professional, civic, or other activities, family, or leisure. Advantages and disadvantages of informal and non-formal education for preschool children are considered. It is established that the flexibility of these forms of education allows children to learn at any time and place, enhancing accessibility to education, especially in the context of inclusive education. Furthermore, the importance of an individual approach is emphasized, enabling consideration of the interests and needs of each child. In informal and non-formal education for preschool children, motivation for learning is developed through the opportunity for independent selection of topics and subjects. Thus, the development of independence is another advantage of informal and non-formal education. However, the drawbacks of these types of education include the risk of misinformation and the absence of normative control, which can lead to the dissemination of unreliable information and stereotypes among children. Therefore, it is crucial to promote the development of critical thinking among preschool children.